Anisotropic mechanical and mass-transport performance of Ti6Al4V plate-lattice scaffolds prepared by laser powder bed fusion. (August 2022) - Wang, Xiaobo; Zhang, Lei; Song, Bo; Zhang, Jinliang; Fan, Junxiang; Zhang, Zhi; Han, Quanquan; Shi, Yusheng
Abstract: In bone scaffolds, the mechanical performance provides the load-bearing capability, and the mass-transport performance presented as permeability dominates the nutrients/oxygen transportation efficiency. Body-centered-cubic and face-centered-cubic plate lattice scaffolds with mechanical and mass-transport performance close to human bones are proposed in the present study. The regular periodic architecture and plane-stress state of the plate lattice scaffolds not only provide them with advanced mechanical properties but avoid stress concentration that ubiquitously exists in traditional truss lattice scaffolds. By investigating the anisotropic mechanical and mass-transport performance of plate lattice scaffolds, a valid regulation strategy is put forward to modulate their performance without changing the volume fraction and architecture, providing an alternative scheme for biomedical scaffold design. Both computational and experimental results demonstrate that body-centered-cubic and face-centered-cubic plate lattice scaffolds possess appropriate mechanical and mass-transport performance close to human bones. In addition, tuning ranges of the mechanical and mass-transport performance of plate lattice scaffolds for different orientations are up to 40% and 45%, respectively. These findings could provide valuable references for the extensive applications of plate lattice scaffolds in bone tissue engineering. Statement of significance: In bone tissue engineering, scaffolds with low density, high strength, and proper permeability are of constant request. The present study proposes body-centered-cubic and face-centered-cubic plate lattice scaffolds with mechanical and mass-transport performance close to human bones. The deformation mechanisms and mass-transport characteristics of plate lattice scaffolds for different orientations are revealed. In addition, a valid regulation strategy is put forward to modulate the mechanical and mass-transport performance of plate lattice scaffolds without changing their volume fraction and architecture, providing an alternative scheme for biomedical scaffold design. We believe that these findings could provide significant guidance for the simultaneous improvements of advanced scaffold designing. Graphical abstract: Image, graphical abstract